EMISI KENDARAAN PADA RUAS JALAN PROVINSI DI JAWA BARAT - Sekaryadi, Yudi; Santosa, Wimpy (Jurnal HPJI, 2017)
Abstract Total greenhouse gas emissions in Indonesia until 2005 was 295.6 megatonnes of CO2 eq. Of these 68 mega tonnes of CO2 eq, or about 23%, were generated by the transport sector. A total of 91% of transport emissions, or as much as 61.88 megatonnes of CO2 eq, comes from road transport emissions. The provincial road in West Java has a total length of 2185.38 km and are spread in 27 districts/cities. The results of this study indicate that emissions from vehicles in provincial roads in West Java was 2.06 megatonnes of CO2 eq, or approximately 3.3% of the emissions of greenhouse gases from road transport in Indonesia came from the provincial roads in West Java. Keywords: greenhouse gas, vehicle emissions, provincial roads  Abstrak Total emisi gas rumah kaca di Indonesia sampai dengan tahun 2005 adalah 295,6 mega ton CO2 eq. Dari jumlah tersebut 68 mega ton CO2 eq, atau sekitar 23%, dihasilkan oleh sektor transportasi. Sebanyak 91% emisi transportasi, atau sebanyak 61,88 mega ton CO2 eq, berasal dari emisi transportasi jalan. Ruas jalan provinsi di Jawa Barat mempunyai panjang total 2.185,38 km dan tersebar di 27 kabupaten/kota. Hasil studi ini menunjukkan bahwa emisi yang berasal dari kendaraan di ruas-ruas jalan provinsi di Jawa Barat adalah 2,06 mega ton CO2 eq atau sekitar 3,3% emisi gas rumah kaca akibat transportasi jalan di Indonesia berasal dari ruas-ruas jalan provinsi di Jawa Barat. Kata-kata kunci: gas rumah kaca, emisi kendaraan, jalan provinsi